Peramalan Permintaan Produk Beras Pandan Wangi Asli dengan Menerapkan Metode Autoregressive Integrated Moving Average (ARIMA) dan Seasonal ARIMA (SARIMA) pada Perusahaan Agriculture Business - Halimah Anis Kurlillah; Adelia Tata Anggita; Nenzy Agustin Dwi Prahesti (Pusat Riset dan Inovasi Nasional, 2024)
Agriculture Business Company is a company that runs in the field of agriculture, in the form of rice or paddy. However, the company focuses more on rice. The company is experiencing problems in meeting consumer demand for original pandan wangi rice which still cannot be fulfilled due to limited raw materials. With this problem, forecasting is carried out using the Autoregressive Integrated Moving Average (ARIMA) and Seasonal Autoregressive Integrated Moving Average (SARIMA) methods. The data used is pandan wangi rice demand data for the period January 2021 to December 2023, with Minitab software as a calculation tool. The results of data processing show that the data obtained is not seasonal, therefore only processing is carried out using the ARIMA method. The research results of the best model in forecasting consumer demand for original pandan wangi rice at the Agriculture Business Company is the ARIMA (0, 1, 1) Model with an MSE value of 34.39. The MSE value is the smallest MSE value for the original pandan wangi rice demand forecasting model at the Agriculture Business Company. The advice given to the company is that from the results of the research, the company can later make a reference in shopping for raw materials and evaluate what factors can increase the value of demand.